Comparison of neurotoxic potency between a novel chinbotulinumtoxinA with onabotulinumtoxinA, incobotulinumtoxinA and lanbotulinumtoxinA in rats - Feng, Ya (Drug Des Devel Ther, 2017)
Four botulinumtoxin type A (BoNT/A) products, onabotulinumtoxinA (A/Ona), incobotulinumtoxinA (A/Inco), lanbotulinumtoxinA (A/Lan) and chinbotulinumtoxinA (A/Chin), are applied in the present study, among which A/Chin is newly produced. We aimed to compare the neurotoxic potency of these toxins by the gauge of muscle strength reduction. Furthermore, potential molecular and cellular mechanisms were also explored. According to our data, muscle strengths in the four toxin groups were all significantly decreased after injection for 1 week. A/Chin achieved the most obvious reduction in muscle strength as compared to the other three products at the dose of 0.5 U. However, there was no difference between the four toxins when increased to 2 U. As the toxins wore off, muscle strength recovered to basal level 12 weeks postinjection. We further measured the expression levels of key factors involved in neuromuscular junction stabilization and muscle genesis. Our results showed that nicotinic acetylcholine receptor, myogenic regulatory factors and muscle-specific receptor tyrosine kinase were all significantly upregulated upon BoNT/A treatment. Consistent with the result of muscle strength, A/Chin had the most obvious induction of gene expression. Moreover, we also found local inflammation response following BoNT/A injection. Owing to lack of complexing proteins, both A/Inco and A/Chin stimulated relatively lighter inflammation compared to that of A/Ona and A/Lan groups. In conclusion, our study provided evidence for the efficacy of the novel A/Chin and its similar functional mode to that of A/Ona, A/Inco and A/Lan. In addition, A/Chin has superiority in inducing muscle paralysis and inflammation stimulation, which may indicate faster onset and longer duration of this novel A/Chin.